2011
DOI: 10.2214/ajr.10.4734
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Gray-Scale Ultrasound for Quantitative Evaluation of Tumor Response to Chemotherapy: Preliminary Results With a Mouse Hepatoma Model

Abstract: Quantitative analysis of tumor blood perfusion with contrast-enhanced ultrasound can be used for noninvasive assessment of functional changes in tumors after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The presence of UCA has proven to be a good overall indicator of blood volume within tumors. 6,[30][31][32] Recently, Needles et al described the development of the VisualSonics PA system and used it to monitor the response of a breast cancer cell line in mice to a targeted anti-angiogenic therapy. 26 The group showed a significant decrease in CEUS-derived tumor vascularity and tumor perfusion as well as PA-derived blood and tissue oxygenation levels between the treatment and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of UCA has proven to be a good overall indicator of blood volume within tumors. 6,[30][31][32] Recently, Needles et al described the development of the VisualSonics PA system and used it to monitor the response of a breast cancer cell line in mice to a targeted anti-angiogenic therapy. 26 The group showed a significant decrease in CEUS-derived tumor vascularity and tumor perfusion as well as PA-derived blood and tissue oxygenation levels between the treatment and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The bolus injection was performed by one radiologist (W.Z., with 3 years of experience in small-animal studies) within 1-2 seconds for all animals, University) of 5 to 6 weeks old, weighing from 16 to 18 g ( 27 ). On the basis of our previous experience with this tumor model ( 28 ), the sample size of 10 mice per treatment group was selected to provide a signifi cant difference in tumor volume of 50% between the control group and the treated groups, with a power fi xed at 0.8 and a type I error of a = .05.…”
Section: Histologic Analysismentioning
confidence: 99%
“…Other than these molecular target drugs, currently most of the cancer patents still undergo the treatment of cytotoxic chemotherapy. We have previously shown that tumor blood flow perfusion changes after cisplatin treatment with CEUS [12]. However, to the best of our knowledge, the value of quantifying tumor blood flow perfusion with CEUS has not been tested in early assessing tumor response to cytotoxic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%